Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Disiplin Kerja pada Karyawan Fakultas Kedokteran dan Kesehatan Universitas Muhammadiyah Jakarta - Eka Lestari (STIKes Ibnu Sina Ajibarang, 2024)
Human Resources is the most privileged asset in a company. This study aims to determine the influence of leadership style and organizational culture on work discipline at FKK UMJ, an institution that operates in the medical education service sector. This type of research uses a quantitative approach with a saturated sample involving 45 respondents. The data collection technique uses observation through questionnaires. The results of this study show that leadership style (X1) has a positive effect on work discipline (Y) by 86.4%, this is evidenced based on the t-value of 16.555 > t-table 2.017 with a significant value of 0.000 < 0.05. Organizational culture (X2) has a positive effect on work discipline (Y) by 78.2%, this is evidenced by the t-value of 12.430 > t.017 table with a significant value of 0.000 < 0.05. Leadership style (X1) and organizational culture (X2) simultaneously (together) had a positive influence on work discipline (Y) by 88.4% and the remaining 11.6% were influenced by variables outside this study. This is evidenced based on the F value of 159.517 > the F value of table 3.22 with a significant value of 0.000 < 0.05.